2010
DOI: 10.1111/j.1445-5994.2009.01912.x
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer patients in Queensland suffer delays in receiving radiation therapy – but not as a result of distance

Abstract: Aim: To determine whether lung cancer radiation therapy waiting times in Queensland public hospitals are associated with distance of residence from the nearest treatment facility. Methods: Retrospective analysis of radiation therapy waiting times of 1535Queensland residents who were diagnosed with lung cancer from 2000 to 2004 and received radiation therapy as initial treatment at a public hospital. The effect of distance of residence from treatment centre on median waiting time was analysed by quantile regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Large cohort studies in Canada have identified waiting times of 42 days for curative radiotherapy and 39 days for surgery. Closer to home, the median overall waiting time from diagnosis to initiation of radiation therapy in Queensland was 33 days; this was not affected by distance to the treating hospital 19 . Median waiting times were longer for patients with early stage disease (stage I and II NSCLC; median, 48 days) than for those with more advanced disease (stages III and IV disease; median, 34 and 26 days respectively).…”
Section: Discussionmentioning
confidence: 92%
“…Large cohort studies in Canada have identified waiting times of 42 days for curative radiotherapy and 39 days for surgery. Closer to home, the median overall waiting time from diagnosis to initiation of radiation therapy in Queensland was 33 days; this was not affected by distance to the treating hospital 19 . Median waiting times were longer for patients with early stage disease (stage I and II NSCLC; median, 48 days) than for those with more advanced disease (stages III and IV disease; median, 34 and 26 days respectively).…”
Section: Discussionmentioning
confidence: 92%
“…We had no information on whether patients received chemotherapy or radiotherapy as these are predominantly provided in outpatient cancer care centres. However, other studies have shown that, like surgery, there is lower use of radiotherapy, chemotherapy and combined treatment with increasing distance to specialist treatment and that their use varies depending on the specialty of the hospital or whether a centre with radiotherapy was the first attended . We also used a cancer registry‐based definition of localized stage (localized to the tissue or organ of origin); TNM definitions would have been preferable but were not available.…”
Section: Discussionmentioning
confidence: 99%
“…RA is just one VMAT technology now available. Australian centres have been plagued by skilled staff shortages and waiting lists [8,9]. VMAT can contribute to solving these problems as well as update our treatment complexity to the level expected of a developed country.…”
Section: Discussionmentioning
confidence: 99%